Operador de recombinação EHR aplicado ao problema da árvore máxima - Faria, Danilo Alves Martins de (2013)
Network Design Problems (NDPs) are present in many areas, such as electric power distribution, communication networks, vehicle routing, phylogenetic trees among others. Many NDPs are classified as NP-Hard problems. Among the techniques used to solve them, we highlight the Evolutionary Algorithms (EA). These algorithms simulate the natural evolution of the species. However, in its standard form EAs have limitations to solve large scale NDPs, or with very specific characteristics. To solve these problems, many researchers have studied specific forms of representation of NDPs. Among these stands we show Node-Depth-Degre Encoding (NDDE). This representation produces only feasible solutions, regardless of the network characteristics. NDDE has two mutation operators Preserve Ancestor Operator (PAO) and Ancestor Change Operator (CAO) and the recombination operator EHR (Evolutionary History Recombination Operator) that uses historical applications of mutation, and was applied to NDPs more than one tree and had good results. Thus, this work proposes adapt EHR for NDPs classics represented by a single tree. In addition, two evolutionary algorithms are developed: the AE-RNPG, which uses only NDDE, with mutation operators. And the AE-EHR, which makes use of mutation operators and recombination operator EHR to the One Max Tree Problem. The results showed that the AE-EHR obtained better solutions than the EA-RNPG for most instances analyzed.